The Mediterranean-dietary approaches to stop hypertension diet intervention for neurodegenerative delay (MIND) diet: a bibliometric analysis - Dai, Linxiong; Lin, Xiaoxiao; Wang, Shuai; Gao, Yue; He, Fei (Frontiers in Nutrition, 2024)
The MIND diet is a healthy dietary pattern that has some benefits for many health outcomes. Our study aims to conduct a bibliometric analysis of the MIND diet, identifying leading edges and hotspots to provide a reference for future research. The research on the MIND diet was gathered from the Web of Science Core Collection (WOSCC) database. For bibliometric analysis, VOSviewer 1.6.16 and the WOSCC Online Analysis Platform were utilized. In total, this comprehensive investigation encompassed 171 documents in the field of the MIND diet. The publications are globally distributed, with contributions from 953 authors across 362 institutions in 37 countries/regions, and published in 94 journals. The United States leads with 72 publications, and Iran and the People's Republic of China also show notable engagement with 28 and 19 publications, respectively. Rush University stands out with 15 publications, followed by Harvard